ANALISIS DEBIT KETERSEDIAAN AIR DI DAS BALO BATAM - Ginting, Jody Martin (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2024)
The rapid development of technology has caused the development of Smart City throughout Indonesia to be intensified. Batam is one of the cities that is aggressively preparing for this. One of the actions taken is to prepare the availability of clean water that is suitable for all its citizens. This study aims to determine how much water availability in one of the watersheds in Batam, namely the Balo watershed. The method used in this study is a quantitative method by analyzing data available in the field such as rain data and discharge data. Discharge data will later be obtained using the synthetic unit hydrograph method that analyzes the hydrograph using data on the flow area and length of the river in the watershed. The rain data and discharge data will be accumulated to produce water availability discharge data. The highest water availability discharge data per year in the Balo watershed occurred in November and the lowest in February and March. The largest availability discharge was 1,963 m3/s and the lowest was 0 m3/s. The results of this calculation are expected to be used by the community or local government to be able to plan for drought or flood disaster mitigation in the Balo watershed or Batam City itself.